PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUASAN PELANGGAN PADA CITRA LAUNDRY KOTA PARIAMAN - Afrianti, Rini (Menara Ilmu, 2017)
The rapid development of the business world has affected the growing number of new business units released by both small and medium-sized and large-scale communities. The phenomenon, is acknowledged by the rapid development of laundry service provision kilogram laundry. The purpose of this study is to determine the quality of service and location to customer satisfaction Citra Laundry Pariaman City. Population used in customer research Citra Laundry. The sample in this research is 30 respondents. Based on testing The test results show that the quality of service and location affect simultaneously or collectively to Customer Satisfaction. based on Determination Coefficient testing that Service Quality and Location have Adjusted R Square value of 30.7%. The analytical method used is multiple linear regression. The result of research can be concluded that multiple linear regression is Y = 1,613 + 0,628X1 + (- 0,032) X2. Partial test results show the variables used in the study of service quality is significant and location does not affect significantly and on customer satisfaction in Citra Laundry Pariaman City. Suggestion of research: 1. So that researcher suggest at Citra laundry that Citra Laundry employee always willing to help customer if happened complaint consumer, by responding and receiving quickly, so Citra Laundry have good service ability. 2) On the image of Laundry store position must be fore or parallel to the store. And the Citra Laundry store needs to do aggressive promotion through social media and other media in order to increase the sales revenue level of those services. 3) Parties Citra Laundry and employees should provide good service in the form of polite, friendly to consumers and a clean place and provide insurance for consumers or customers in case of errors from the store Citra Laundry in the form of replacing goods or unag cash. 4) For further research is expected to dapet more develop research conducted is doing research on other variables that affect customer satisfaction. Keywords: Service Quality, Location and Customer Satisfaction